Symmetry-controlled reversible photovoltaic current flow in ultrathin all 2D vertically stacked graphene/MoS2/WS2/graphene devices - Zhou, Y; Xu, W; Sheng, Y; Huang, H; Zhang, Q; Hou, L; Shautsova, V; Warner, J (American Chemical Society, 2019)
Atomically thin vertical heterostructures are promising candidates for optoelectronic applications, especially for flexible and transparent technologies. Here, we show how ultrathin all two-dimensional vertical-stacked type-II heterostructure devices can be assembled using only materials grown by chemical vapor deposition, with graphene (Gr) as top and bottom electrodes and MoS2/WS2 as the active semiconductor layers in the middle. Furthermore, we show that the stack symmetry, which dictates the type-II directionality, is the dominant factor in controlling the photocurrent direction upon light irradiation, whereas in homobilayers, photocurrent direction cannot be easily controlled because the tunnel barrier is determined by the doping levels of the graphene, which appears fixed for top and bottom graphene layers due to their dielectric environments. Therefore, the ability to direct photovoltaic current flow is demonstrated to be only possible using heterobilayers (HBs) and not homobilayers. We study the photovoltaic effects in more than 40 devices, which allows for statistical verification of performance and comparative behavior. The photovoltage in the graphene/transition-metal dichalcogenide-heterobilayer/graphene (Gr/TMD-HB (MoS2/WS2)/Gr) increases up to 10 times that generated in the monolayer TMD devices under the same optical illumination power, due to efficient charge transfer between WS2 and MoS2 and extraction to graphene electrodes. By applying external gate voltages ( Vg), the band alignment can be tuned, which in turn controls the photovoltaic effect in the vertical heterostructures. The tunneling-assisted interlayer charge recombination also plays a significant role in modulating the photovoltaic effect in the Gr/TMD-HB/Gr. These results provide important insights into how layer symmetry in vertical-stacked graphene/TMD/graphene ultrathin optoelectronics can be used to control electron flow directions during photoexcitation and open up opportunities for tandem cell assembly.